PENGARUH SOSIAL – EKONOMI DARI SENTRA INDUSTRI KECIL : KASUS DI KAB. BANTUL, JOGJAKARTA - Fereshti Nurdiana Dihan; Edy Purwo Saputro (Universitas Muhammadiyah Semarang, 2011)
An analysis of a small industry is a wide variety and refers to developing and empowering; therefore, in along term, it can be autonomous in a strict competition. The study aims to examine a small industry performance ofchips in Banguntapan District, Bantul Regency, Jogjakarta. The study is useful for describing the characteristics ofindustry specifically. It was a qualitative approach with data gathering through depth-interview with key person.The findings of the study indicate that UKM (middle-small sized industry) in a variety of forms has differentcharacteristics. However, there are a number of serious problems for sustainability. Some problems are a license,location and capital since a majority of UKM is not bankable, a lack of human resources including regeneration andsuccession for sustainability, dualistic leadership as owner as well as manager, serious management problem –incredible accounting, pay standard, raw-material assurance, additional product, marketing aspect and waste ofproduction.A further research needs to design all problems referring to the findings of the UKM cases in industrycenter for chips. Although the generalization of the findings is not broad, it shows a classical problem of UKM toneed analyzing more intensively for answering the problem. For a further research, thus, it is necessary to includeall of the parties to find a solution for the continuity of UKM that can positively contribute to labor marketrecruitment and micro and macro economy improvement. However, the study is limited to the case so that thegeneralization can not be reached. The conclusion, but, can concretely describe a variety of problems.